Effect of Sodium Oxybutyrate on Mesentery Microcirculation and Liver Metabolism in Hemorrhagic Stroke (Experimental Study) - A. K. Korzhevskaya; V. O. Nikolsky; L. V. Boyarinova (Общая реаниматология)
Objective: to study the effect of sodium oxybutyrate on canine mesentery microcirculation and liver metabolism in hemorrhagic stroke. Materials and methods. The investigation was based on the examination of specimens taken from 72 dogs of both sexes, weight 15.5±1.5 kg. Hypovolemic hypotension was induced by free bloodletting via the femoral artery. Systolic blood pressure was lowered to 40 mm Hg and maintained at the same level during an hour by the Wiggers procedure. The magnitude of blood loss was 31—33 ml/kg. The dogs were divided into 4 groups: 1) intact (n=5); 2) one-hour hypovolemic hypotension (n=8); 3) control (n=31), in which physiological saline was intravenously injected at a concentration of 0.9—1.1 ml/kg an hour after hypovolemic hypotension; 4) experimental (n=28), in which 10% sodium oxybutyrate solution was intravenously injected at a concentration of 180—200 mg/kg an hour after hypovolemic hypotension. In Groups 1 and 2 dogs, as well as in the control and experimental groups, divided into 2 subgroups, in which laparotomy was carried out under local 0.25% novocaine solution in combination with intravenous sodium thiopental (15—20 mg/kg) an hour after the drug administration and an hour after blood reinfusion, then right liver lobe pieces were excised for histochemical and biochemical studies. In Groups 3 and 4, heparinized blood was reinfused an hour after administration of the agent. The animals were observed during an hour. In the dogs from the latter two groups, mesentery vascular microcirculation was evaluated at control time stages, by using biomicroscopy on a MBR-1 microscope-based unit. Results. Despite uncompensated blood loss, the use of sodium oxybutyrate in hemor-rhagic stroke improves microcirculation in the mesentery vessels. In the liver, it enhances the rate of reactions of oxida-tive phosphorylation and the pentose phosphate pathway, activates glucose uptake processes, prevents lactate accumulation, preserves glycogen stores, and elevates the content of high-energy phosphates. Conclusion. Administration of 10% sodium oxybutyrate solution at concentrations of 180-200 mg/kg an hour after hypovolemic hypotension prevents the progression of mesentery microcirculatory disorders and hepatic metabolic changes during the following hour of hemorrhagic stroke. Blood loss compensation during previous administration of sodium oxybutyrate promotes a fuller and more rapid recovery of mesentery microcirculation and hepatic metabolic processes in the early postresuscitative period. Key words: hemorrhagic stroke, sodium oxybutyrate, microcirculation, metabolism, liver.